The Routledge Companion to Innovation Management - Chen, Jin; Brem, Alexander; Viardot , Eric; Kam Wong, Poh (Routledge Companions in Business, Management and Accounting, 2019)
Innovation contributes to corporate competitiveness, economic performance and environmental sustainability. In the Internet era, innovation intelligence is transferred across borders and languages at an unprecedented rate, yet the ability to benefit from it seems to become more divergent among different corporations and countries. How much an organization can benefit from innovation largely depends on how well innovation is managed in it. Thus, there is a discernible increase in interest in the study of innovation management. This handbook provides a comprehensive guide to this subject. The handbook introduces the basic framework of innovation and innovation management. It also presents innovation management from the perspectives of strategy, organization and resource, as well as institution and culture. The book's comprehensive coverage on all areas of innovation management makes this a very useful reference for anyone interested in the subject.